2020
DOI: 10.1515/hmbci-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of 12- and 24-session cardiac rehabilitation on physical, psychosocial and biomedical factors in ischemic heart disease patients

Abstract: BackgroundCardiac rehabilitation (CR) is a key component of effective care for patients with a wide spectrum of cardiac problems. It seems that the short-term provision of these services can facilitate their use and meeting of related needs for patients participating in the CR programs.Materials and methodsIn this interventional study on patients with ischemic heart disease (IHD) referred to the Cardiac Rehabilitation Center of Chamran Hospital, Isfahan, Iran. One-hundred and twelve patients were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…In general, the results of this study showed that the cardiac rehabilitation program is important in the secondary prevention of CVD and cardiac rehabilitation can increase the functional capacity of heart patients in all age groups and different subgroups by activating physiological mechanisms such as oxygen uptake from the blood, increasing the oxidative response and increasing cardiac output [25] [26]. Among anthropometric, clinical and psychologic indices, gender variable, level of primary depression and EF less than 35 were identified as the most effective indicators affecting the improvement of functional capacity.…”
Section: Discussionmentioning
confidence: 74%
“…In general, the results of this study showed that the cardiac rehabilitation program is important in the secondary prevention of CVD and cardiac rehabilitation can increase the functional capacity of heart patients in all age groups and different subgroups by activating physiological mechanisms such as oxygen uptake from the blood, increasing the oxidative response and increasing cardiac output [25] [26]. Among anthropometric, clinical and psychologic indices, gender variable, level of primary depression and EF less than 35 were identified as the most effective indicators affecting the improvement of functional capacity.…”
Section: Discussionmentioning
confidence: 74%
“…Resultados de um estudo clínico recente, que comparou os efeitos da RC com durações diferentes, 12 e 24 semanas sobre a composição corporal, mostraram que apenas aqueles que realizaram 24 semanas de programa reduziram significativamente peso corporal, IMC e circunferência abdominal (SADEGHI et al, 2020). Este achado sugere que períodos mais prolongados de treinamento físico podem ser necessários para alcançar bons resultados na composição corporal.…”
Section: Reabilitação Cardiovascular E Melhora Dos Fatores De Risco Cardiovascularesunclassified